2015
DOI: 10.1517/17425247.2015.999038
|View full text |Cite
|
Sign up to set email alerts
|

Self-nano-emulsifying drug delivery systems: an update of the biopharmaceutical aspects

Abstract: The utilization of SNEDDS to augment the oral bioavailability of poorly water-soluble drugs goes beyond improvement in drug's solubility, as was initially presumed. In fact, SNEDDS have a potential to increase oral bioavailability by multi-concerted mechanisms such as reduced intra-enterocyte metabolism by CYP P450 enzymes, reduced P-glycoprotein (P-gp) efflux activity and hepatic first-pass metabolism bypass via lymphatic absorption. This unique biopharmaceutical point of view, presented in this review, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 92 publications
1
75
0
2
Order By: Relevance
“…By this way drugs delivered by SEDDS may bypass first pass metabolism. All these abovementioned mechanisms are well-depicted in the review published by Cherniakov et al (2015).…”
Section: Lipidsmentioning
confidence: 82%
See 2 more Smart Citations
“…By this way drugs delivered by SEDDS may bypass first pass metabolism. All these abovementioned mechanisms are well-depicted in the review published by Cherniakov et al (2015).…”
Section: Lipidsmentioning
confidence: 82%
“…However, outcomes of these pharmacokinetic studies have been rarely summarized and addressed in recent times. In a nice scientific description, Cherniakov et al (2015) discussed the biopharmaceutical points of SEDDS after its oral administration. The review was primarily focused on the absorption, bioavailability and disposition of drugs delivered by oral SMEDDS/SNEDDS (Cherniakov et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the charge on tiny globules definitely affects the extent of absorption from the negatively charged mucosal surface. [33] Zeta potential values suggested that microemulsions were stable and less likely to pose any problem in the short span of processing in GI tract (GIT). As the drug is already in dissolved form within the formulation, the onset of absorption will be faster.…”
Section: Zeta Potential Measurementmentioning
confidence: 99%
“…In a study by Patel et al (2011), SNEDDS system was able to induce in vivo absorption by 7.5 folds 7 . Moreover, the oil based system will escape pHrelated influence of the GI tract thus ideal as a formulation for oral adminitration 8 . In spite of the beneficial effects of the nanocarriers on living cells, undesirable effects may occur.…”
Section: Introductionmentioning
confidence: 99%